Asparagus racemosus (Shatavari): A Versatile Female Tonic - Sharma, Komal (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Asparagus racemosus, traditionally known as shatavari means "who possesses a hundred husbands or acceptable to many". In Ayurveda it is considered a female tonic. In spite of being a rejuvenating herb it is beneficial in female infertility, as it increases libido, cures inflammation of sexual organs and even moistens dry tissues of the sexual organs, enhances folliculogenesis and ovulation, prepares the womb for conception, prevents miscarriages, acts as post partum tonic by increasing lactation and normalizing the uterus and the changing hormones. Its use is also advocated in leucorrhoea and menorrhagia. Shatavari is the main Ayurvedic rejuvenative tonic for the females, as is Withania for the males.